2021
DOI: 10.1007/s15010-021-01626-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 4-year intervention on hand hygiene compliance and incidence of healthcare associated infections: a longitudinal study

Abstract: Purpose Studies have demonstrated improvements in hand hygiene (HH) compliance through interventions, noting the negative association of HH and healthcare associated infections (HAIs), but how to sustain long-term improvement is still unknown in the Chinese population. This study sought to determine the extent of change in HH compliance after multimodal HH interventions, and to evaluate the relationship between that change and HAI incidence. Methods We conducted a longitudinal study in a general teaching hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…[18] A Chinese longitudinal study from 2017 to 2020 in a provincial general teaching hospital showed that improvement in HH compliance was associated with a decline in the incidence of HAIs. In this study the compliance of hand hygiene increased form 68.9-91.76%, and the incidence of HAIs decreased from 1.1-0.91%, p < 0.01 [19] . A historical control study in China showed the adherence of hand hygiene and mask-wearing during the COVID-19 pandemic (from February 1 to June 29, 2020) increased from 66-92%.…”
Section: Discussionsupporting
confidence: 46%
“…[18] A Chinese longitudinal study from 2017 to 2020 in a provincial general teaching hospital showed that improvement in HH compliance was associated with a decline in the incidence of HAIs. In this study the compliance of hand hygiene increased form 68.9-91.76%, and the incidence of HAIs decreased from 1.1-0.91%, p < 0.01 [19] . A historical control study in China showed the adherence of hand hygiene and mask-wearing during the COVID-19 pandemic (from February 1 to June 29, 2020) increased from 66-92%.…”
Section: Discussionsupporting
confidence: 46%
“…It has earlier been reported that the incidence of HAIs begins to decrease on the hospital level once monthly HHC exceeds 80% for two years [9]. In a recent four-year longitudinal Chinese study, HHC increased from 64.8% to 90.5% as a result of direct observations and immediate feedback [18]. They observed a weak but statistically significant negative correlation (r ¼ À0.27) between monthly HHC and HAI incidence.…”
Section: Discussionmentioning
confidence: 93%
“…According to a four-year study from a teaching hospital in China, direct observations and immediate feedback increased doctors' monthly HHC to levels as high as 92.2% [18]. Hence, continuous observations and feedback may dispel resistance among doctors and change their HH behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Thorough hand hygiene is important for effective contact transmission prevention, which is one of the primary causes of the spread of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and influenza A virus (IAV). Previous studies have shown that SARS-CoV-2 is more stable (survives longer) on human skin surfaces than IAV, suggesting that appropriate hand hygiene practices are important for SARS-CoV-2 infection control . However, it is difficult to ensure adherence to frequent and proper hand hygiene practices even in hospitals or clinics and improving these adherence rates remains challenging. The introduction of new infection control approaches may help achieve reliable prevention of contact transmission. For example, if the disinfection effect of disinfectants persists on the skin surface for a long time after hand hygiene practices, this residual disinfection effect (RDE) may reduce the risk of contact transmission by inactivating the virus on the skin surface without further intervention, even if hand hygiene practices are not followed immediately after accidental exposure to infectious substances.…”
Section: Introductionmentioning
confidence: 99%